High performance piezoelectric crystal cut designed using LiNbO3 for high temperature acoustic emission sensing application. Issue 3 (24th December 2021) - Wang, Guoliang; Xie, Linfang; Jiang, Chao; Liu, Xueliang; Li, Yanlu; Yu, Fapeng; Zhao, Xian
Abstract : An optimal piezoelectric crystal cut designed using LiNbO3 possessed stable electro-elastic performance over a wide temperature range of 20–500 °C. Abstract : Lithium niobate (LiNbO3, LN) is a kind of multifunctional crystal material. In this study, an optimum piezoelectric crystal cut ( XZt /28°) with a central resonance frequency of 150 kHz and stable electro-elastic performance over a wide temperature range of 20–500 °C was explored. Furthermore, a piezoelectric acoustic emission sensor was designed and fabricated using the optimum crystal cut, followed by Hsu–Nielsen tests for potential high-temperature structural health monitoring (SHM). The fabricated acoustic emission sensor was found to show a high response for detecting the Lamb wave both at room temperature and a high temperature of 500 °C, and the peak-to-peak values were obtained to be as high as 69.8 mV and 41.3 mV, respectively. Significantly, the signal-to-noise ratio (SNR) value of the sensor was evaluated to be >20 dB at a high temperature of 500 °C. The above results support that the LN-based piezoelectric acoustic emission sensor is promising for high-temperature structural health monitoring.